The Effect of Gamification Method on vocabulary Achievement of Junior High School Students - Hariyanto, Medico Torikul Khakam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This research project explores the use of gamification techniques as a teaching tool, particularly with reference to the platform Bamboozle. Gamification techniques are not widely used in Indonesia, especially in rural and suburban areas with little access to educational resources. The purpose of this research is to assess how well gamification might improve students' language skills and provide useful information for researchers and educators. The research involved 25 participants who volunteered to contribute to the study. Quantitative research methods were use, specifically pre- and post-experimental research, utilizing tests consisting of 15 to 20 multiple-choice questions and 5 essay questions. The results indicated a significant improvement in the participants' vocabulary achievements following the implementation of the Bamboozle-based treatment. The treatment was more successful than the researchers were expecting, proving that gamification techniques especially those utilizing Bamboozle are effective at improving learning outcomes. This study emphasizes how gamification might help with educational difficulties, especially in resource-poor areas. It also emphasizes how crucial it is to use cutting-edge teaching techniques in order to enhance students' educational experiences and results. Future research could examine how gamification affects education in the long run and how it can be used in a variety of learning settings.